Fusing Mobile Phone Sensing and Brain Imaging to Assess Depression in College Students - Huckins, Jeremy F.; daSilva, Alex W.; Wang, Rui; Wang, Weichen; Hedlund, Elin L.; Murphy, Eilis I.; Lopez, Richard B.; Rogers, Courtney; Holtzheimer, Paul E.; Kelley, William M.; Heatherton, Todd F.; Wagner, Dylan D.; et al. (Frontiers in Neuroscience, 2019)
As smartphone usage has become increasingly prevalent in our society, so have rates of depression, particularly among young adults. Individual differences in smartphone usage patterns have been shown to reflect individual differences in underlying affective processes such as depression (Wang et al., 2018). In the current study, we identified a positive relationship between smartphone screen time (e.g. phone unlock duration) and resting-state functional connectivity (RSFC) between the subgenual cingulate cortex (sgCC), a brain region implicated in depression and antidepressant treatment response, and regions of the ventromedial/orbitofrontal cortex (OFC), such that increased phone usage was related to stronger connectivity between these regions. We then used this cluster to constrain subsequent analyses looking at individual differences in depressive symptoms in the same cohort and observed partial replication in a separate cohort. Similar analyses were subsequently performed on metrics of circadian rhythm consistency showing a negative relationship between connectivity of the sgCC and OFC. We believe the data and analyses presented here provide relatively simplistic preliminary analyses which replicate and provide an initial step in combining functional brain activity and smartphone usage patterns to better understand issues related to mental health. Smartphones are a prevalent part of modern life and the usage of mobile sensing data from smartphones promises to be an important tool for mental health diagnostics and neuroscience research.